Compulsory vaccination policies: a systematic review about knowledge, attitudes and believes. (13th November 2019) - Voglino, G; Gualano, M R; Bert, F; Olivero, E; Corezzi, M; Rossello, P; Vicentini, C; Siliquini, R
Abstract: Background: Vaccine hesitancy is a considerable issue in European Countries and leads to low coverage rates. Consequently, the implementation of national immunization programmes including the introduction of compulsory vaccination are required. It is interesting to determine citizens' knowledge, attitudes and believes about vaccination policies, in order to more effectively define vaccination programs. Methods: The present study systematically reviewed published studies evaluating attitudes towards mandatory vaccination programs. PubMed and Scopus scientific databases were searched and 4, 198 results were returned, of these 29 met the inclusion criteria. PRISMA statements were followed. Results: Twenty-two studies assessed attitudes towards mandatory vaccination programs in general, while 9 papers focused specifically on the Human Papilloma Virus (HPV) vaccine. Most of the studies were performed in Europe and North America. According to the assessed studies, the majority of the population seems to be in favour of compulsory vaccinations, from 53% to 97% for different vaccination programs. More resistance has been recorded for the HPV vaccination: the percentage of agreement for mandatory HPV vaccinations ranged from 27% to 63.5%. Furthermore, some studies investigated healthcare workers' attitudes towards childhood and adult vaccinations. They pointed out that the general population is generally more in favour of mandatory vaccination policies than healthcare workers. The studies highlighted that the support to mandatory policies increased after their implementations. Conclusions: The results presented in this review could be an important starting point to further understand the issue of vaccine hesitancy and support the implementation of effective vaccination strategies in Europe. Key messages: Mandatory vaccination policies are generally well accepted among general population. More resistance is recorded for specific vaccination (HPV) or among specific population (healthcare workers).